واقع استخدام نموذج الجدارة الائتمانية 18C'S في اتخاذ قرار منح التسهيلات الائتمانية بالمصارف التجارية الليبية": "دراسة حالة الإدارة العامة مصرف الوحدة" - بوعظمات, محمد أصميدة أحمدي محمد; البدري, فوزي سعد نجم; محمد, المبروك خالد (Tobruk University Journal of Social and Human Sciences, 2023)
The study aims to examine the extent to which the creditworthiness model C's18 was used in making the decision to grant credit facilities of commercial banks in Libya , and the study population consisted of Libyan commercial banks, the study sample was limited to (Wahda Bank in Libya) and the employees were selected in the credit and risk departments of the Wahda Bank in Libya and its branches The study sample consisted of 80 employees who work in credit and risk managementFor this reason, and due to the small size of the study sample, a comprehensive survey method was used, to ensure results closer and more generalizable, To achieve the aim of the study, a questionnaire was designed and developed for the purpose of collecting data from the sample, and the Statistical Package for Social Sciences (SPSS) was used to analyze the data using descriptive analysis that relies on studying the phenomenon as it exists in reality. One of the most important findings of this study is that the Libyan commercial banks under study use the 18C's creditworthiness model in deciding to grant credit facilities. Among the most important recommendations of this study is the need to focus more on applying this model in all Libyan commercial banks.